2020
DOI: 10.1051/shsconf/20207403003
|View full text |Cite
|
Sign up to set email alerts
|

The role of electronic word-of-mouth in influencing consumer repurchase intention in social commerce

Abstract: This research investigates the way consumer repurchase intention in social commerce is shaped by electronic word-of-mouth at global scale. Building our argument by drawing on data collected from Deloitte, eMarketer, MarketingCharts, Marketing Insider Group, McKinsey, Mediakix, Nielsen, Smart Insights, and Statista, we performed analyses and made estimates regarding trusted information sources according to consumers, products/services that Internet users have personally recommended to others, channels through w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…As stated, the arrival of social media and its usage for decision-making is not apart from the influences of gender. Those who want to purchase the products through online retailers prefer to check what existing consumer say about their experiences, which further help them to make the decision accordingly ( Anastasiei and Dospinescu, 2019 ; Ismagilova et al., 2019 ; Lăzăroiu et al., 2020 ; Zhenquan and Xueyin, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…As stated, the arrival of social media and its usage for decision-making is not apart from the influences of gender. Those who want to purchase the products through online retailers prefer to check what existing consumer say about their experiences, which further help them to make the decision accordingly ( Anastasiei and Dospinescu, 2019 ; Ismagilova et al., 2019 ; Lăzăroiu et al., 2020 ; Zhenquan and Xueyin, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further to (Du et al, 2020) brand awareness can affect repurchase intention on the basis of knowledge of online services. The power of WoM is also an instrument for determining online repurchase intention behaviour (Lăzăroiu et al, 2020). In the context of online shopping, repurchase intention is an opportunity for someone who will continue to do it in the future (Pham et al, 2018).…”
Section: Repurchase Intentionmentioning
confidence: 99%
“…In the current era of online media, electronic wordof-mouth (eWOM) spreads like viral marketing, and it spreads faster and wider than traditional word-ofmouth [5][6][7]. eWOM and online reviews are the best channels for consumers to instantly respond with postconsumer psychological cognition about service organization communication and repurchase intentions [8][9][10][11][12]. The research results of many previous studies have shown that the long-term impact of the word-of-mouth effect of online reviews is far greater than that of traditional marketing activities and media exposure [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%